(untitled) (Archaeologia Adriatica, 2023)
Island archaeology is a dynamic and innovative field of research focused on the study of numerous issues related to island communities, cultures and environment. Despite all the research potential that the islands provide, it is known that the Croatian islands have been poorly explored in archaeological terms. In contrast to numerous selective approaches focused on individual sites or periods, rare islands have been the subject of systematic research focused on the entire island landscape. As a result of such considerations, the student research project “Archaeological landscape of the island of Ist - Archaeo.IST” was launched in 2020 with the aim of analyzing the archaeological landscape of the island of Ist as a complex and multi-layered “archive” of data that can testify to the dynamic past of the island. With its geographical position as part of the wider Zadar archipelago, its small area and heterogeneous landscape with a high level of preservation, the island of Ist provided an ideal testing site for conducting systematic research. The preliminary results of the field survey made it possible to gain insight into the complexity of the island’s landscape, provided a basis for monitoring the dynamics of population and use of the island from prehistoric times to the late Middle Ages, and at the same time opened the door to new perspectives on understanding the interactions of human communities in the marginal environments of small Adriatic islands.